Caracterização fundiária e dimensionamento de florestas de Acacia mearnsii de Wild na metade sul do Rio Grande do Sul - Pasa, Débora Luana (2018)
The Acacia mearnsii (black-wattle) is an important species in the Rio Grande do Sul (RS) economy, since the bark can be harnessed for tannin extraction and wood for the manufacture of paper and cellulose, particle boards, charcoal and firewood and stands out for being present in the rural properties of many families. The present study was carried out in 29 municipalities in the southern half of the State of RS and aimed at quantifying Acacia reforestation, characterizing the reforestation land management profile and identifying criteria that define it, as well as analyzing the concentration of planted areas and generating prognoses in relation to the installed supply and consumption capacity of black-wattle. Through the classification of Landsat 8 satellite images from the years 2016 and 2017, 34,211.00 hectares of black-wattle were quantified, obtaining an accuracy of 0.91 by the Kappa Index. Through the application of questionnaires, it was possible to identify that 31.81% of the reforestations are in leased areas and 68.19% in their own area. Of the total number of interviewees, 9.09% consider forestry activity as the main source of income, 40.08% as a complementary activity and 50% do not consider Acácia planting an important factor in determining income. The discriminant analysis characterized two distinct groups of producers: "Profile to continue reforesting (a)" and "Profile not to continue to reforest (b)", with 56.81% intending to continue in the forestry sector and 43.18% will not continue to reforest. It was noted that the market for black-wattle was drastically affected by the global crisis of 2008, but there is currently a large availability of raw material which reduces the price paid for reforestation. The analysis related to the supply and demand of raw material found that the reforested area would currently have around 2 to 3 years of consumption. Given the 43.18% trend of producers to stop reforesting, this figure should be even more aggravating. The calculated Gini Index showed a high concentration of reforested areas, with an average value of 0.72. Finally, it was verified that the profile of the of the producers of Acácia is changing, since the plantations are no longer belonging to small producers, migrating to large reforestations linked mainly to forest-based companies, fact evidenced by the high concentration of areas